GLCM texture analysis on different color space for pterygium grading - Che Azemin, Mohd Zulfaezal; Mohd Tamrin, Mohd Izzuddin; Hilmi, Mohd Radzi; Mohd. Kamal, Khairidzan (Asian Research Publishing Network (ARPN), 2015)
GLCM texture features have been widely used to characterize biomedical images. Most of the previous studies using GLCM features to characterize biomedical images only consider single or limited color space due to the use of only one color model. To mimic human color perception, conventional RGB color model may need to be supplemented with other color space models for better human vision representation. This study is aimed to find an optimal set of GLCM features extracted from different color space for pterygium grading. Mimicking human color perception has commonly employed RGB color space, which is shown in this paper is inadequate. GLCM features when extracted in various color space show better representation of human perception (correlation coefficient > 0.6) compared to using RGB color space (correlation coefficient < 0.2).